Magnetic field dispersion in the neighbourhood of Bok Globules. Issue Volume 9:Issue S302(2013) (7th August 2014) - Rodrigues, C. V.; Magalhães, V. de S.; Vilas-Boas, J. W.; Racca, G.; Pereyra, A.
Abstract: We performed an observational study of the relation between the interstellar magnetic field alignment and star formation in twenty (20) sky regions containing Bok Globules. The presence of young stellar objects in the globules is verified by a search of infrared sources with spectral energy distribution compatible with a pre main-sequence star. The interstellar magnetic field direction is mapped using optical polarimetry. These maps are used to estimate the dispersion of the interstellar magnetic field direction in each region from a Gaussian fit, σ B . In addition to the Gaussian dispersion, we propose a new parameter, η, to measure the magnetic field alignment that does not rely on any function fitting. Statistical tests show that the dispersion of the magnetic field direction is different in star forming globules relative to quiescent globules. Specifically, the less organised magnetic fields occur in regions having young stellar objects.